Relatório de estágio curricular supervisionado em medicina veterinária - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The Supervised Curricular Internship in Veterinary Medicine (ECSMV) is a mandatory constituent for the graduation in Veterinary Medicine. The site chosen by the trainee for the ECSMV was the University Veterinary Hospital (HVU) of the Federal University of Santa Maria (UFSM) in the area of ​​small animal medical clinic, located in building 97B, Av. Roraima, 1,000, Camobi Neighborhood , Santa Maria - RS. HVU's hours of operation are Monday through Friday, from 7:30 am to 7:30 pm, offering care in various areas and specialties: small-group medical and surgical clinics, anesthesiology, neurology, ophthalmology, physiotherapy, orthopedics, laboratory analysis of clinical and veterinary pathology, imaging diagnostic sector, in addition to the ruminant clinical and equine clinical sectors. The activities related to the traineeship were related to the participation and follow-up of the clinical services in the HVU, which occurred from February 15, 2016 to May 6, 2016, making up the total workload of 478 hours. The ECSMV was supervised by Prof. Dr. Anne Santos do Amaral, Director of the University Veterinary Hospital, and institutional orientation of Prof. Dr. João Paulo of the Pascon Exaltation. A total of 306 visits were performed, including 256 canines and 56 felines, as well as several activities related to the routine of the small animal clinic, such as 242 blood collection, 53 inpatient management, follow-ups to the imaging sector, being 77 radiographic examinations , 59 sonography and 2 echocardiography, among other activities. The ECSMV acted as a complement to the technical training of the academic, aiming at a better preparation for insertion in the job market, besides putting in practice the knowledge received during graduation and obtaining new learning. The present work aims to present the activities developed during the supervised curricular internship in veterinary medicine in the area of ​​small animal medical clinic.
Report of supervised internship in veterinary medicine
Keywords: Medicina veterinária; Clínica veterinária; Pequenos animais; CNPQ::CIENCIAS AGRARIAS